Upaya Meningkatkan Kualitas Pembelajaran Guru Melalui Supervisi Kelas di TK Negeri 1 Kota Banda Aceh Tahun Pelajaran 2021/2022 - Hazal Fitri; Sarniyati Yusmanita; Ulil Azmi (Al Yazidiy Jurnal Sosial Humaniora dan Pendidikan, 2022)
Supervision has a central position in efforts to foster and develop collaborative activities in an educational organization. This requires the principal to have more abilities as a supervisor to improve the quality of learning in schools. The aim of this research is to determine the application of classroom supervision in improving the quality of learning in TK Negeri 1 Banda Aceh City for the 2021/2022 academic year. This research is school action research using qualitative descriptive methods. The subjects in this school action research were all teachers in TK Negeri 1 Banda Aceh City, totaling 12 teachers. The data collection techniques used were observation, interviews and documentation studies. The research results showed that the teacher's ability to manage learning in cycle I was 2.69 which was quite good. In the second cycle, it was seen that the teacher's ability to manage learning had increased to good, namely 4.16. In the first cycle, student activity was only 55%, then in the second cycle there was an increase in an even better direction from the first cycle, namely 80%. In cycle I, students were said to be incomplete, because classical completion reached 64%, whereas in cycle II there was an increase in an even better direction, namely the percentage reached 93%, and students were said to be complete. Based on the research results, it can be concluded that implementing class supervision measures can improve the quality of learning in TK Negeri 1 Banda Aceh City for the 2021/2022 academic year.